No rain, no flowers [compact disc] (Warner Records, 2025)
Collaborating with iconic songwriters such as Rick Nowels and Daniel Tashian and legendary keys player Scott Storch, the Grammy-winning Ohio band crafted their most ambitious and adventurous album yet, braiding together the pair's sprawling, eclectic musical influences.